Efektivitas Konseling Kelompok Singkat Berfokus Solusi untuk Meningkatkan Tanggung Jawab Siswa dalam Belajar - Villa Silvi; Hidayat Maruf; Widiya Aris Radiani (Al Washliyah : Jurnal Penelitian Sosial dan Humaniora, 2023)
This study aims to determine the effectiveness of short group counseling focused on solutions to increase student responbility in learning. This study used a quantitative experimental approach with the type of pre-experiment design design one group pretest-posttest. The sample in this study was 6 students of class XI IIS SMAN 2 Puruk Cahu. Data collection techniques in this study used a scale of learning responbility, interviews, observation and documentation. The results of the study showed that there were differences between before and after being given treatment. Before being given treatment the average value was 56,07%. After being given treatment it became 68,45%, meaning that the percentage of students responbility in learning increased by 12,38% after being given treatment. Meanwhile based on the results of the paired T-Test, a signicance value of 0,002 < 0,05 was obtained, so it can be concluded that Ha is accepted so that solution Focused Brief Group Conseling is effective for increasing students responbility in learning at SMAN 2 Puruk Cahu.